Dry eye disease caused by viral infection: review - Alves,Monica (2013)
Dry eye disease and ocular surface disorders may be caused or worsened by viral agents. There are several known and suspected virus associated to ocular surface diseases. The possible pathogenic mechanisms for virus-related dry eye disease are presented herein. This review serves to reinforce the importance of ophthalmologists as one of the healthcare professional able to diagnose a potentially large number of infected patients with high prevalent viral agents.